Coalescence of multiple pairs of levitated droplets using dual-side phased arrays - Jianqing Li; Nicholas J. Goddard; Ruamsiri Songsaeng; Ruchi Gupta (Ultrasonics Sonochemistry)
Acoustic levitation in air and contactless coalescence of levitated droplets using acoustic forces are of great significance to chemical and biological reactions. The state-of-the-art is levitation and coalescence of 3 pairs of droplets achieved via dual-side phased arrays. However, there are no reports on the general design principles for manipulation and coalescence of > 3 pairs of droplets. Equally, there are no reports on sequential coalescence of more than two columns of droplets, which is essential for performing reactions requiring addition of more than two reagents. In this paper, we showed that wide traps are more suited than narrow traps for the coalescence of droplets. In wide traps, the acoustic energy was expanded along the direction of merging of droplets. Additionally, uniform traps created in this work by distributing energy between traps increased the number of droplets that can be levitated. We have reported a new algorithm named DS-PAT based on direct search method to overcome the limitations of existing algorithms. Using wide uniform traps and the DS-PAT algorithm, for the first time, a stable coalescence of up to 6 pairs of levitated droplets was achieved. To measure experimental acoustic fields during the merging process, a custom-built acoustic scanning setup was employed, which showed good consistency with simulations. Subsequently, DS-PAT was used to design the sequential coalescence of 4 columns of droplets with 2 droplets in each column. This was then applied to study the well-known oscillatory Belousov–Zhabotinsky (BZ) reaction. This work gives general principles of designing acoustic fields for stable coalescence of columns of droplets and introduces a global algorithm for dual-side phased arrays, paving the way for stable and efficient chemical and biological reactions in airborne droplets.